Outcome Measures for Evaluating the Effect of a Multidisciplinary Intervention on Axial Symptoms of Parkinson's Disease - Bouça-Machado, Raquel; Pona-Ferreira, Filipa; Gonçalves, Nilza; Leitão, Mariana; Cacho, Ricardo; Castro-Caldas, Ana; Ferreira, Joaquim J.; and CNS Multidisciplinary Team (Frontiers in Neurology, 2020)
Introduction: Satisfactory symptomatic control of Parkinson’s disease (PD) axial symptoms remains challenging. As they represent an important cause of disability, new management strategies should be tested. To that, the selection of outcomes to be measured and reported in a clinical trial is crucial. In this study, we aim to identify the most responsive outcome measures to assess the effectiveness of a multidisciplinary intervention on PD patients’ axial symptoms. Methods: PD patients engaged in a multidisciplinary intervention program, were assessed at admission and discharge by a multidisciplinary team. The responsiveness to change and the smallest sample size needed to enable conclusive results were studied for each outcome. Results: Twenty-two patients were included in the study. The effect size detected varied between 0.04 and 0.83. Sample size calculations, for 90% power and assuming 30% of change from baseline, ranged from 8 to 180 participants. Conclusions: The MDS-UPDRS part III and total score and the 10-meter walk test were the outcomes with better responsiveness to a multidisciplinary intervention and requiring a small number of participants to enable conclusive results. A larger trial is needed to clarify the suitability of the TUG test.